Automated exchange compared to manual and simple blood transfusion attenuates rise in ferritin level after 1 year of regular blood transfusion therapy in chronically transfused children with sickle cell disease. Issue 11 (19th August 2020) - Kelly, Shannon; Rodeghier, Mark; DeBaun, Michael R.
Abstract: Background: Optimal strategies for regular blood transfusion therapy are not well defined in sickle cell disease (SCD). This analysis tested the hypothesis that in the first of year of regular transfusions, when chelation therapy use is minimal, automated exchange transfusion would be the superior method for attenuating the rise in ferritin levels compared to simple and manual exchange transfusions. Study design and methods: The Silent Cerebral Infarct Multi‐Center Clinical Trial randomly allocated children with SCD and silent cerebral infarcts to receive standard care or regular transfusions with a target pre‐transfusion HbS concentration ≤ 30% and minimum hemoglobin level > 9.0 g/dL. Participants with at least nine transfusions and sufficient ferritin testing in the first year of the trial were included in a planned secondary analysis. Ferritin levels by the end of the first study year were compared between participants receiving automatic exchange transfusion, manual exchange transfusion, and simple transfusion. Results: A total of 83 participants were analyzed. During the first year of the study, 75.9% of the participants had >80% of transfusions via one transfusion method. At baseline no significant differences in ferritin levels were observed in the three transfusion groups (p = 0.1). After 1 year of transfusions the median (interquartile range) ferritin levels in the simple transfusion (n = 40), manual exchange transfusion (n = 34) and automatic exchange transfusion (n = 9) groups were 1800 ng/mL (1426‐2204 ng/mL), 1530 ng/mL (1205‐1805 ng/mL), and 355 ng/mL (179‐579 ng/mL), respectively (p < 0.001). Conclusion: Automated exchange transfusion, when compared to other transfusion methods, is the optimal transfusion strategy for attenuating increase in ferritin levels in children with SCD.